2019
DOI: 10.3897/jhr.74.47315
|View full text |Cite
|
Sign up to set email alerts
|

Plagiolepis alluaudi Emery, 1894, a globally spreading exotic ant (Hymenoptera, Formicidae) newly recorded from Tenerife (Canary Islands, Spain)

Abstract: Citation: Staab M (2019) Plagiolepis alluaudi Emery, 1894, a globally spreading exotic ant (Hymenoptera, Formicidae) newly recorded from Tenerife (Canary Islands, Spain). Journal of Hymenoptera Research 74: 83-91. https://doi. AbstractExotic ants have been a prevalent ecological problem, particularly in tropical and subtropical islands. Here Plagiolepis alluaudi Emery, 1894 is recorded from the island of Tenerife (Canary Islands, Spain) for the first time, where it was commonly encountered in the town Puerto d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Except for Technomyrmex pallipes and Strumigenys membranifera, the rest of the species here reported have never been discovered before in the Macaronesian archipelagos. In addition, two other new exotic ants detected in our survey and recently reported by other authors, namely Plagiolepis alluaudi (Staab, 2019) and Lepisiota frauenfeldi (Schifani et al, 2018), were genetically confirmed, and their distribution is broadened to other islands.…”
Section: Re Sultssupporting
confidence: 87%
See 2 more Smart Citations
“…Except for Technomyrmex pallipes and Strumigenys membranifera, the rest of the species here reported have never been discovered before in the Macaronesian archipelagos. In addition, two other new exotic ants detected in our survey and recently reported by other authors, namely Plagiolepis alluaudi (Staab, 2019) and Lepisiota frauenfeldi (Schifani et al, 2018), were genetically confirmed, and their distribution is broadened to other islands.…”
Section: Re Sultssupporting
confidence: 87%
“…Although Schifani et al (2018) and Staab (2019) have already reported L. frauenfeldi and P. alluaudi, respectively, our data allow us to genetically confirm the identity of the species. They show their establishment and spread in the archipelago by detecting their presence in more locations and islands.…”
Section: Species Confirmationmentioning
confidence: 55%
See 1 more Smart Citation
“…Donisthorpe (1930) had also described Cardiocondyla bicolor from Israel but this was later synonymised with C. obscurior (Seifert 2003). It was first recorded for Macaronesia from Puerto de la Cruz, Tenerife in the Canary Islands in 1999 (Seifert 2003), where it was also recorded by Staab (2009), and very recently from Cape Verde (Wetterer and Espadaler 2021). However, Wetterer and Espadaler (2021) provide information on a species of Cardiocondyla reported by Collingwood and Van Harten (1993) from Cape Verde, which differ from Cardiocondyla emeryi, and have 'tentatively assumed' that these correspond to C. obscurior.…”
Section: Resultsmentioning
confidence: 99%
“…All three species are exotics. Furthermore, the three have been recorded from the nearby Canary Islands (Seifert 2003;Staab 2009;Espadaler and Fernández 2014;Hernández-Teixidor et al 2020) and therefore, their presence is not unexpected. Pheidole navigans is also reported to be spreading across the Southeastern United States (Sarnat et al 2015) and the records from Macaronesia represent part of a more general expansion of the species.…”
Section: Discussionmentioning
confidence: 94%